PERFORMANCE OF CERTIFIED LECTURERS IN IMPLEMENTING PAIKEMI STRATEGIES IN ISLAMIC SCIENCES IN ISLAMIC STATE UNIVERSITIES - Amin, Muhammad; Najminnur Hasanatun Nida; Taufiqurrahman (CV. ADIBA AISHA AMIRA, 2024)
This research is a qualitative study that aims to describe and explain how the performance of certified lecturers in implementing an active learning PAIKEMI model that takes place in the lecture process. This research took place at the Islamic State University of Antasari Banjarmasin, especially at the Faculty of Tarbiyah and Keguruan, and targeted Islamic courses. The data collection process was carried out by means of observation, interviews, and documentation. In the first stage, data would be taken by observing how certified lecturers deliver their lectures in the classroom and then initiating interviews and questionnaires with them as well as with students to capture how their perceptions during lectures take place in the second stage. The third stage was analyzing the lesson plans (RPS) that lecturers have made before entering the classroom. The results of this study were as follows: 1) A large number of lecturers were already aware of contextual-based learning methods such as giving students the freedom to discuss, making the physical environment of the classroom conducive, and conducting periodic evaluations, all of which are felt to increase student motivation and trigger student creativity. 2) There were some lecturers who still implement traditional modes during lectures such as the lecture method, which is very monotonous for students so they have limited opportunities to actively participate during lectures.